ISSP 2015 - Work orientations IV: Sweden - Edlund, Jonas (Umeå University, 2017)
This survey is the Swedish part of the 2015 'International Social Survey Program' (ISSP), and it is the fourth time an ISSP-survey is focusing on Work Orientations.

The International Social Survey Program, ISSP is a continuing annual programme of cross-national collaboration on surveys covering topics important for social science research. It brings together pre-existing social science projects and coordinates research goals, thereby adding a cross-national, cross-cultural perspective to the individual national studies.

Since its start in 1985, the attitudes toward a wide range of different subjects have been studied. Some themes have returned through the years, making it possible to compare them over time. The following topics have been discussed:

1985 The Role of Government I
1986 Social Networks I
1987 Social Inequality I
1988 Family and Changing Gender Roles I
1989 Work Orientations I
1990 The Role of Government II
1991 Religion I
1992 Social Inequality II
1993 Environment I
1994 Family and Changing Gender Roles II
1995 National Identity I
1996 The Role of Government III
1997 Work Orientations II
1998 Religion II
1999 Social Inequality III
2000 Environment II
2001 Social Networks II
2002 Family and Changing Gender Roles III
2003 National Identity II
2004 Social Citizenship I
2005 Work Orientations III
2006 Role of Government IV
2007 Leisure and Sports I
2008 Religion III
2009 Social Inequality IV
2010 Environment III
2011 Health
2012 Family, Work and Gender Roles IV
2013 National Identity
2014 Citizenship

Purpose:

ISSP aims to design and implement internationally comparable attitude surveys. The study in 2015 is focussing on Work orientations.

Detta är den svenska studien inom det internationella forskningsprojektet ISSP. Temat för studien 2015 är ”Vilka är dina åsikter om jobben och arbetslivet?”. Detta är fjärde gången studien genomförs på det här temat.

International Social Survey Program, ISSP, är ett globalt forskningsprojekt som har till uppgift att konstruera och genomföra internationellt jämförbara attitydstudier. Sedan 1985 har attityddata årligen samlats in och utgör nu en databas som är fritt tillgänglig för forskarsamhället. I dagsläget är 48 länder, från sex olika världsdelar, involverade i projektet. Genom bredden av medlemsländer skapas möjlighet till jämförelser i flera dimensioner. Det finns möjligheter att både jämföra länder som har en likartad samhällsstruktur och historia, och länder som skiljer sig påtagligt från varandra.

Sverige har varit medlem i ISSP sedan 1992 och det är Sociologiska institutionen vid Umeå universitet som är huvudman för studierna i Sverige.

Sedan starten 1985 har attityder från flera olika områden undersökts. Vissa områden har återkommit genom åren, vilket gör det möjligt att även jämföra dem över tid. Följande ämnen har behandlats:

1985 The Role of Government I
1986 Social Networks I
1987 Social Inequality I
1988 Family and Changing Gender Roles I
1989 Work Orientations I
1990 The Role of Government II
1991 Religion I
1992 Social Inequality II
1993 Environment I
1994 Family and Changing Gender Roles II
1995 National Identity I
1996 The Role of Government III
1997 Work Orientations II
1998 Religion II
1999 Social Inequality III
2000 Environment II
2001 Social Networks II
2002 Family and Changing Gender Roles III
2003 National Identity II
2004 Social Citizenship I
2005 Work Orientations III
2006 Role of Government IV
2007 Leisure and Sports I
2008 Religion III
2009 Social Inequality IV
2010 Environment III
2011 Health
2012 Family, Work and Gender Roles IV
2013 National Identity
2014 Medborgarskap

Syfte:

ISSP har som syfte att konstruera och genomföra internationellt jämförbara attitydstudier. Studien för 2015 undersöker åsikter om jobben och arbetslivet.
ISSP 2015 - Åsikter om jobben och arbetslivet
Keywords: occupations; yrken; employment; anställning; wages; löner; discrimination; diskriminering; family life; familjeliv; labour and employment; arbete och sysselsättning; workplace; arbetsplats; labour market; arbetsmarknad; career development; karriärutveckling; businesses; företag; workplace relations; arbetsplatsförhållanden; career; karriär; hours of work; arbetstid; CORS; CORS; Political behaviour and attitudes; Politiska beteenden och attityder; International politics and organisations; Internationell politik och organisationer; Social welfare systems/structures; Sociala välfärdssystem/-strukturer; Social behaviour and attitudes; Socialt beteende och attityder; Social Sciences; Samhällsvetenskap; Sociology; Sociologi